2022
DOI: 10.3389/fneur.2022.724641
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preinjury Use of Antiplatelet Drugs on Outcomes of Traumatic Brain Injury: A Systematic Review and Meta-Analysis

Abstract: ObjectiveThe study aimed to compare outcomes of traumatic brain injury (TBI) in patients on pre-injury antiplatelet drugs vs. those, not on any antiplatelet or anticoagulant drugs.MethodsPubMed, Embase, and Google Scholar databases were searched up to 15th May 2021. All cohort studies comparing outcomes of TBI between antiplatelet users vs. non-users were included.ResultsTwenty studies were included. On comparison of data of 2,447 patients on pre-injury antiplatelet drugs with 4,814 controls, our analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, the subgroup of patients on dual antiplatelet therapy had an increased delayed bleeding risk, compared with single APA patients [ 364 ]. Another meta-analysis that included 20 observational studies comparing 2447 TBI patients on pre-injury APAs with 4814 controls revealed no statistically significant difference in early mortality, need for neurosurgery or LOS between the two groups, with similar results for subgroup analyses of aspirin and clopidogrel users [ 365 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the subgroup of patients on dual antiplatelet therapy had an increased delayed bleeding risk, compared with single APA patients [ 364 ]. Another meta-analysis that included 20 observational studies comparing 2447 TBI patients on pre-injury APAs with 4814 controls revealed no statistically significant difference in early mortality, need for neurosurgery or LOS between the two groups, with similar results for subgroup analyses of aspirin and clopidogrel users [ 365 ].…”
Section: Resultsmentioning
confidence: 99%
“…With this regard, several authors emphasise that anti-platelets vs. anticoagulants, and amongst the latter, VKAs vs. DOACs, are at higher risk (4,13,22,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Eine aktuelle Metaanalyse zeigte, dass die Einnahme von Thrombozytenaggregationshemmern keinen Einfluss auf die frühe Sterblichkeitsrate bei Patienten mit SHT hatte. Es konnte auch kein Unterschied zwischen Clopidogrel und Aspirin hinsichtlich ihrer Auswirkungen auf die Sterblichkeit bei SHT-Patienten gefunden werden [48].…”
Section: Merkeunclassified